Soil and dasometric characterization of a Eucalyptus globulus Labill plantation and management proposal in the lower montane thorny steppe zone, Riobamba, Ecuador - Guallpa, Miguel; Rosero, Sonia; Samaniego, María; Cevallos, Eduardo (Enfoque UTE, 2016)
There is limited information on the growth and yield of the Tasmanian blue gum plantation in Tunshi-ESPOCH homestead in varying physiographic conditions, soil properties and management; for this reason it was decided to assess its forest mass. Circular plots were installed with 12.62 m radius at an intensity of 5-6% ha-1. Through systematic unaligned sampling for lifting dasometric information and digging three pits stand-1, using stratified sampling for variables of the place. The application of statistical estimators, determined at an altitude of 2755 amsl, a total average tree volume estimated-1 of 2.32 m3 compared with 0.25 m3 at an altitude of 2929 amsl. Two areas of conservation and other forest use were defined. There are significant associations between total unit volume of T. blue against altitude, organic matter content, cationic exchange capacity at surface level and level of boron underlying level, generating a management strategy for each defined area.